2021
DOI: 10.1177/00111287211054718
|View full text |Cite
|
Sign up to set email alerts
|

Re-Opening Dallas: A Short-Term Evaluation of COVID-19 Regulations and Crime

Abstract: We investigated the relationship between COVID-19 stay-at-home regulations and property and violent crime indexes in Dallas, TX during the first 6 months of 2020. We tested for changes in property and violent crime trends using four key “intervention” dates: the stay-at-home order issued by Judge Clay Jenkins (March 24), the start of Governor Abbott’s phase one of re-opening (May 1), a second phase of more widespread re-openings (May 18), and a third phase of increased capacity limits for businesses (June 3). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Riddell et al (2021) examined changes in property and violent crime offenses in Dallas, TX across the first 6 months of 2020, composing four separate COVID-19-related phases of government response: (1) stay-at-home order, (2) phase I re-opening allowing 25% capacity for restaurants, movie theaters, museums, libraries, non-essential retail, and shopping malls, (3) phase II re-opening of gyms office workplaces and manufacturing facilities to 25% capacity, and (4) phase III re-opening of businesses to 50% capacity. Employing both Poisson regression leveraging daily crime counts and trend analysis using the start dates of each of the four phases of re-opening, Riddell et al (2021) found initial stay-at-home orders led to a 6.8% decrease in daily violent crime counts and a 7% to 10% decrease in property crime yet found an increasing trend for both violent and property crime between the initial stay-at-home order and the phase I re-opening, and that phase III (reopen all businesses to 50% capacity) was associated with higher daily counts of both violent and property crime (18.5% increase in violent crimes and 12%-15% increase in property crimes). This study advances our knowledge surrounding the pandemic and associated governmental restrictions' influence on different crime types, but, more importantly, is one of the first to examine the influence of both restrictions and the easing of such restrictions on crime.…”
Section: Changes In Crime Counts and Calls For Servicementioning
confidence: 99%
“…Riddell et al (2021) examined changes in property and violent crime offenses in Dallas, TX across the first 6 months of 2020, composing four separate COVID-19-related phases of government response: (1) stay-at-home order, (2) phase I re-opening allowing 25% capacity for restaurants, movie theaters, museums, libraries, non-essential retail, and shopping malls, (3) phase II re-opening of gyms office workplaces and manufacturing facilities to 25% capacity, and (4) phase III re-opening of businesses to 50% capacity. Employing both Poisson regression leveraging daily crime counts and trend analysis using the start dates of each of the four phases of re-opening, Riddell et al (2021) found initial stay-at-home orders led to a 6.8% decrease in daily violent crime counts and a 7% to 10% decrease in property crime yet found an increasing trend for both violent and property crime between the initial stay-at-home order and the phase I re-opening, and that phase III (reopen all businesses to 50% capacity) was associated with higher daily counts of both violent and property crime (18.5% increase in violent crimes and 12%-15% increase in property crimes). This study advances our knowledge surrounding the pandemic and associated governmental restrictions' influence on different crime types, but, more importantly, is one of the first to examine the influence of both restrictions and the easing of such restrictions on crime.…”
Section: Changes In Crime Counts and Calls For Servicementioning
confidence: 99%